2022
DOI: 10.3389/fcell.2022.768356
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Selective Packaging of Host RNA and Viral RNA Modification in SARS-CoV-2 Viral Preparations

Abstract: Viruses package host RNAs in their virions which are associated with a range of functions in the viral life cycle. Previous transcriptomic profiling of host RNA packaging mostly focused on retroviruses. Which host RNAs are packaged in other viruses at the transcriptome level has not been thoroughly examined. Here we perform proof-of-concept studies using both small RNA and large RNA sequencing of six different SARS-CoV-2 viral isolates grown on VeroE6 cells to profile host RNAs present in cell free viral prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Hypotheses 3: The Nsp5-TRMT1 interaction could allow the virus to bind tRNAs that are packaged in viral particles as suggested previously (Pena et al, 2022). The finding that expression of the non-cleavable TRMT1-Q530N variant enhances viral replication and infectivity supports the hypothesis that TRMT1 could facilitate tRNA uptake into viral particles.…”
Section: Author Contributionssupporting
confidence: 55%
“…Hypotheses 3: The Nsp5-TRMT1 interaction could allow the virus to bind tRNAs that are packaged in viral particles as suggested previously (Pena et al, 2022). The finding that expression of the non-cleavable TRMT1-Q530N variant enhances viral replication and infectivity supports the hypothesis that TRMT1 could facilitate tRNA uptake into viral particles.…”
Section: Author Contributionssupporting
confidence: 55%
“…The inhibition of host translation may be beneficial to certain viruses that can locally maintain a tRNA pool optimized for viral translation (Hernandez-Alias et al , 2021; Pavon-Eternod et al , 2013; van Weringh et al , 2011; Yang et al , 2021). Another possibility is that Nsp5-TRMT1 interaction facilitates the packaging of specific tRNAs into viral particles as suggested previously (Pena et al ., 2022). The observation that expression of the non-cleavable TRMT1-Q530N variant enhances viral replication and infectivity supports the hypothesis that TRMT1 could facilitate tRNA uptake into viral particles.…”
Section: Discussionmentioning
confidence: 67%
“…In a recent study, Chikungunya RNA virus infection has been shown to increase the expression of a human tRNA modification enzyme and alter tRNA modification patterns to favor viral protein expression (Jungfleisch et al , 2022). Interestingly, SARS-CoV-2 viral particles exhibit an enrichment of specific host tRNAs with distinct modification profiles (Pena et al , 2022). Moreover, analysis of RNA extracted from human nose swabs have identified tRNA profiles and modification signatures associated with mild versus severe COVID-19 (Katanski et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Chikungunya RNA virus infection has been shown to increase the expression of a human tRNA modification enzyme and alter tRNA modification patterns to favor viral protein expression (Jungfleisch et al, 2022). Interestingly, SARS-CoV-2 viral particles exhibit an enrichment of specific host tRNAs with distinct modification profiles (Pena et al, 2022). Moreover, analysis of RNA extracted from human nose swabs have identified tRNA profiles and modification signatures associated with mild versus severe COVID-19 (Katanski et al, 2022).…”
Section: Introductionmentioning
confidence: 99%